Does Balloon Kyphoplasty Deliver More Cement Safely into Osteoporotic Vertebrae with Compression Fractures Compared with Vertebroplasty? A Study in Vertebral Analogues - Abduljabbar, Fahad H. (Global Spine J, 2015)
Study Design A biomechanical and radiographic study using vertebral analogues. Objectives Kyphoplasty and vertebroplasty are widely used techniques to alleviate pain in fractures secondary to osteoporosis. However, cement leakage toward vital structures like the spinal cord can be a major source of morbidity and even mortality. We define safe cement injection as the volume of the cement injected into a vertebra before the cement leakage occurs. Our objective is to compare the amount of cement that can be safely injected into an osteoporotic vertebra with simulated compression fracture using either vertebroplasty or balloon kyphoplasty techniques. Methods Forty artificial vertebral analogues made of polyurethane with osteoporotic cancellous matrix representing the L3 vertebrae were used for this study and were divided into four groups of 10 vertebrae each. The four groups tested were: low-viscosity cement injected using vertebroplasty, high-viscosity cement injected using vertebroplasty, low-viscosity cement injected using balloon kyphoplasty, and high-viscosity cement injected using balloon kyphoplasty. The procedures were performed under fluoroscopic guidance. The injection was stopped when the cement started protruding from the created vascular channel in the osteoporotic vertebral fracture model. The main outcome measured was the volume of the cement injected safely into a vertebra before leakage through the posterior vascular channel. Results The highest volume of the cement injected was in the vertebroplasty group using high-viscosity cement, which was almost twice the injected volume in the other three groups. One-way analysis of variance comparing the four groups showed a statistically significant difference (p < 0.005). Conclusions High-viscosity cement injected using vertebroplasty delivers more cement volume before cement leakage and fills the vertebral body more uniformly when compared with balloon kyphoplasty in osteoporotic vertebrae with compression fractures.